Development of a Cell‐Based Gene Therapy Approach to Selectively Turn Off Bone Formation. Issue 11 (31st July 2017) - Alvarez‐Urena, Pedro; Zhu, Banghe; Henslee, Gabrielle; Sonnet, Corinne; Davis, Eleanor; Sevick‐Muraca, Eva; Davis, Alan; Olmsted‐Davis, Elizabeth
ABSTRACT: Cell and gene therapy approaches are safer when they possess a system that enables the therapy to be rapidly halted. Human mesenchymal stem cells were transduced with an adenoviral vector containing the cDNA for bone morphogenetic protein 2 (AdBMP2) to induce bone formation. To make this method safer, a system to quickly kill these virally transduced cells was designed and evaluated. Cells were encapsulated inside poly(ethylene glycol) diacrylate (PEG‐Da) hydrogels that are able to shield the cells from immunological destruction. The system involves an inducible caspase‐9 (iCasp9) activated using a specific chemical inducer of dimerization (CID). Delivering AdBMP2‐transduced human mesenchymal stem cells encapsulated in PEG‐Da hydrogel promoted ectopic ossification in vivo, and the iCasp9 system allowed direct control of the timing of apoptosis of the injected cells. The iCasp9‐CID system enhances the safety of delivering AdBMP2‐transduced cells, making it a more compelling therapeutic for bone repair and spine fusion. J. Cell. Biochem. 118: 3627–3634, 2017. © 2017 Wiley Periodicals, Inc. Abstract : Cell and gene therapy approaches are safer when they possess a system that enables the therapy to be rapidly halted. Delivering AdBMP2‐transduced human mesenchymal stem cells encapsulated in PEG‐Da hydrogel promoted ectopic ossification in vivo, and the iCasp9 system allowed direct control of the timing of apoptosis of the injected cells. The iCasp9‐CID system enhances the safety of delivering AdBMP2‐transduced cells, making it a more compelling therapeutic for bone repair and spine fusion.